Comparative Study Between Tubularized Incised Plate Urethroplasty and the Meatal Advancement and Glanuloplasty in Coronal Hypospadias: A Single Centre Study - Fatima, Syeda Midhat; Shehzad, Muhammad; Faqeer Muhammad, Hafiza Ayesha; Malik, Huma; Aamir, Muhammad Uzair; Mirza, Hamza Hussain; Chaudhry, Muhammad Amjad (Biological and Clinical Sciences Research Journal, 2025)
Coronal hypospadias is a common congenital anomaly of the male urethra, for which multiple surgical techniques exist. Tubularized Incised Plate (TIP) urethroplasty and Meatal Advancement and Glanuloplasty Incorporated (MAGPI) are commonly employed methods, each with distinct operative characteristics and outcome profiles. However, data comparing their effectiveness, particularly in cases of isolated coronal hypospadias, remains limited in the Pakistani context. Objective: To compare the operative efficiency, postoperative outcomes, complications, cosmetic results, and parental satisfaction between TIP and MAGPI techniques in pediatric patients with coronal hypospadias. Methods: This prospective comparative study included 84 male pediatric patients diagnosed with isolated coronal hypospadias at a tertiary care hospital from November 10, 2024, to May 10, 2025. Patients were randomised into two equal groups: Group A (TIP urethroplasty) and Group B (MAGPI). All procedures were performed under general anesthesia following standardized protocols. Postoperative follow-up was conducted at 1 week, 1 month, 3 months, and 6 months to assess operative time, complications, cosmetic outcomes (HOSE score), functional voiding, and parental satisfaction. Statistical analysis was performed using SPSS version 26.0. Results: The mean age of participants was 3.7 ± 1.8 years. MAGPI had a significantly shorter mean operative time (36.8 ± 6.4 min) compared to TIP (56.2 ± 7.9 min; p<0.001). Complication rates, including urethrocutaneous fistula, meatal stenosis, and glanular dehiscence, were slightly lower in the MAGPI group, although not statistically significant. Both groups demonstrated high rates of excellent-to-good cosmetic outcomes (TIP: 92.9%, MAGPI: 97.6%) and parental satisfaction (TIP: 90.5%, MAGPI: 95.2%). Functional voiding was achieved in 97.6% (TIP) and 100% (MAGPI). Overall success rates were 90.5% for TIP and 95.2% for MAGPI. Conclusion: Both TIP and MAGPI techniques provide excellent outcomes in the surgical management of coronal hypospadias. However, MAGPI is associated with significantly shorter operative times and comparable—if not slightly superior—outcomes in terms of complications and parental satisfaction. It may therefore be preferred in appropriately selected patients with distal hypospadias and favorable anatomical features.